Infrared small-target detection under a complex background based on a local gradient contrast method - Yang, Linna; Xie, Tao; Liu, Mingxing; Zhang, Mingjiang; Qi,Shuaihui; Yang, Jungang (Zielona Góra: Uniwersytet Zielonogórski)
Small target detection under a complex background has always been a hot and difficult problem in the field of image processing. Due to the factors such as a complex background and a low signal-to-noise ratio, the existing methods cannot robustly detect targets submerged in strong clutter and noise. In this paper, a local gradient contrast method (LGCM) is proposed. Firstly, the optimal scale for each pixel is obtained by calculating a multiscale salient map.
Keywords: small target detection; local gradient contrast; visual saliency; infrared image processing